К вопросу об истории русско-французских литературных связей : Мериме и Пушкин - Юрченко, Ю.В.; Гавришева, Г.П. (Культура народов Причерноморья, 2014)
Статья посвящена проблеме рецепции русской литературы во Франции в XIX веке. В
частности, речь идёт об истории заочного знакомства Проспера Мериме, известного французского
прозаика, и Александра Пушкина, которое произошло благодаря Сергею Соболевскому, близкому другу
российского поэта. Недостаточно исследованная проблема изучения переводческой деятельности
Проспера Мериме определяет актуальность представленной публикации. Стаття присвячена проблемi рецепції російської літератури у Франції в XIX столітті.
Зокрема, мова йде про історію заочного знайомства Проспера Меріме, відомого французького прозаїка,
і Олександра Пушкіна, яке відбулося завдяки близькому другу російського поета Сергію Соболевському.
Недостатньо досліджена проблема вивчення перекладацької діяльності Проспера Меріме визначає
актуальність презентованої публікації. The article is devoted to the problem of the reception of the Russian literature in France in XIX
century. In the article, the process of reception of the A. S. Pushkin`s oeuvre in the French cultural thesaurus is
being. In particular, the authors write about the history of the by-correspondence acquaintance of Prosper
Mérimée, a famous French prose writer, and Alexander Pushkin, a celebrated Russian poet, which happened
due to Sergey Sobolevskiy, Pushkin`s close friend. One reflects the role and place of Prosper Mérimée`s
translation activities, which deepen the idea of his creative work and allow to estimate his contribution to the
development of the dialogue of the Russian and French cultures. The actuality of the publication is defined by
insufficient researches problem of study Prosper Mérimée`s translation activities. It is known that interaction of
cultures is shown in the most different forms, including in the form of mutual literary translations which are
considered by right as one of the main forms of literary interrelations between the people. The special sense is
made by Merimee's contacts with the Russian writer - A.S. Pushkin. The value of each of them - Merimee and
Pushkin is defined by many factors connected with specifics and a stage of development of each of national
literatures. But, being put near to each other - in a context of communications - these writers form special unity
of an executable role - solved esthetic tasks - formations of the world literature.